(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
To date, endometrial hyperplasia (hereinafter referred to as EH) is considered the most common disease in gynecology. Timely complex diagnostics of endometrial pathology allows to achieve good results of treatment: stabilization and elimination of pathological foci, thus preserving and restoring reproductive function.